Recent advances in covalent organic frameworks (COFs) as a smart sensing material. (30th August 2019) - Liu, Xigui; Huang, Danlian; Lai, Cui; Zeng, Guangming; Qin, Lei; Wang, Han; Yi, Huan; Li, Bisheng; Liu, Shiyu; Zhang, Mingming; Deng, Rui; Fu, Yukui; et al.
Abstract : Recent advances in covalent organic frameworks (COFs) as a smart sensing material are summarized and highlighted. Abstract : As a newly emerging kind of porous material, covalent organic frameworks (COFs) have drawn much attention because of their fascinating structural features ( e.g., divinable structure, adjustable porosity and total organic backbone). Since the seminal work of Yaghi and co-workers reported in 2005, the COF materials have shown superior potential in diverse applications, such as gas storage, adsorption, optoelectronics, catalysis, etc. Recently, COF materials have shown a new trend in sensing fields. This critical review briefly describes the synthesis routes for COF powders and thin films. What's more, the most fascinating and significant applications of COFs in sensing fields including explosive sensing, humidity sensing, pH detection, biosensing, gas sensing, metal ion sensing, and other substance sensing are summarized and highlighted. Finally, the major challenges and future trends of COFs with respect to their preparation and sensing applications are discussed.